The number of zoeal stages in larval development of Nihonotrypaea petalura (Stimpson, 1860) (Decapoda: Axiidea: Callianassidae) from Russian waters of the Sea of Japan - Kornienko, Elena S.; Korn, Olga M.; Golubinskaya, Darya D. (Zootaxa, 2015)
Zoeal stages of the mud shrimp Nihonotrypaea petalura (Stimpson, 1860) (Decapoda: Axiiidea: Callianassidae) inhabiting Peter the Great Bay (Sea of Japan) is described and illustrated from the larvae reared in the laboratory individually. The development included seven zoeal stages before molting to the megalopa. At 22–23°C the first megalopa was attained 26 days after hatching. A range of the number of zoeal stages in the family Callianassidae is analyzed. The possibility of variation of the number of zoeal stages of burrowing shrimps in different populations of the same species and/or under different laboratory conditions is discussed.